Application of Extreme Programming Methodology in the Development of a Web-Based Mortality Reporting System with the Laravel Framework - Iin Inarotul Huda; Yuyun Yunengsih; Falaah Abdussalaam (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2025)
Hospital mortality data management directly influences service quality and strategic decision-making capabilities. While electronic medical records have become standard practice in healthcare facilities, existing systems frequently lack the adaptive features necessary for efficient mortality reporting. We address these limitations through the development of a web-based mortality reporting system using Extreme Programming (XP) methodology and the Laravel Framework. The development process engaged two primary user groups: nurses responsible for data entry and medical record officers managing validation and reporting. Black-box testing validated system functionality against operational requirements. Performance evaluation revealed substantial operational gains: patient data entry time decreased from 7-10 minutes to 2-3 minutes, duplicate validation transitioned from manual verification to automated real-time checking, and quarterly report generation reduced from 2-3 hours to 10-20 seconds. The XP methodology, particularly pair programming practices, accelerated defect resolution and enhanced system responsiveness to user feedback. These results demonstrate that iterative development approaches combined with modern web frameworks can fundamentally transform healthcare data management workflows, replacing error-prone manual processes with reliable, efficient digital solutions.